Manajemen lnflasi Indonesia Menuju Optimalitas Growth Ekonomi Nasional - Rozaq, Ibrahim Kholilul Rohman Havid; Soekardjono, Satria Utama; Mahfudz, Nurkholis (Jurnal Ekonomi dan Pembangunan Indonesia, 2002)
In the economic literature, the relationship between the growth and inflation has been discussed in different ways with respect to the development stages of the world economy. According to the current view, there is a negative relationship between growth and inflation. This seems to be compatible with the fact that the investments and the economic growth have been negatively affected by the high and chronic inflation rates. Thus, improvement of the long-run growth potential depends on the elimination of the uncertainties that stems from high inflation rates. Developments in commodity, service, and financial markets necessitate the countries to perceive the world as a global market. The countries (or provinces in our study now) that appraise this process of decentralizations could improve their living standards economically and socially if and only if they manage inflation well hence the economic cost and social cost both are minimize for sustainable growth in each province.